The Influence of Transformational Leadership and Physical Work Environment on Employee Performance with Work Discipline as an Intervening Variable at the Babat Toman Sub-District Office, Musi Banyuasin Regency - Agung Fitrio; Ronal Apriyanto; Rudi Azhar (CV. Proaksara Global Transeduka, 2025)
The main objective of this research is to analyze how transformational leadership and the physical work environment impact employee performance, while also considering work discipline as a connecting factor at the Babat Toman District Office in Musi Banyuasin Regency. Utilizing a quantitative method with an associative approach, the study involved 40 employees as the research population, selected through simple random sampling. Primary data were obtained through structured questionnaires and analyzed using SmartPLS 3. The findings suggest that transformational leadership does not have a significant impact on employee performance when work discipline is taken into account. This implies that work discipline does not play a role as a mediator in this particular connection. On the other hand, the physical work setting has a positive influence on employee performance by way of work discipline, demonstrating that work discipline successfully acts as a mediator between the physical work environment and employee performance.